Teacher shortage in Croatia - a challenge for educational policy, initial teacher education and educational institutions - Domović, Vlatka; Drvodelić, Maja (European journal of teacher education, 2025)
The aim of this paper is to analyse teacher shortage in Croatia and ways in which educational policy reacts to teacher shortage in early childhood education and primary education. This paper presents descriptive study of current national shortage situation and a content analysis of national education policy documents. The data analyses reveal a significant shortage of early childhood education and care (ECEC) teachers. In the first phase of compulsory education there is no shortage of class teachers, while in the second phase of compulsory education exists a permanent shortage of all subject teacher profiles, predominantly from the STEM area. Key educational policy documents analysis reveals the lack of a national strategy for attracting teachers to the profession. Pending a systemic solution, preschool institutions and schools are forced to solicit and employ unqualified staff for teaching positions, whilst the consequences of employing non-professional staff remain uncertain.